Homocysteine as a Marker of Cerebrovascular Diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Hyperhomocysteinemia is a common and modifiable risk factor for cerebrovascular disease. The literature data presented in the review confirms the contributing role of hyperhomocysteinemia in the development of pathology of the cerebrovascular system, as well as the importance of taking into account, in this regard, disorders of homocysteine metabolism when carrying out primary and secondary prevention of athero- and thrombovascular complications. This involves leading a healthy lifestyle with limiting foods that increase homocysteine levels, adhering to the principles of a balanced diet with increased consumption of plant-based foods rich in folic acid and B vitamins. It is also advisable to control homocysteine levels in patients who are taking medications that affect vitamin folate status.